Involvement of Women in Natural Resource Collection in Rural Jharkhand, India. (June 2016) - De, Utpal Kumar; Ghosh, Bhola Nath
Women living in rural areas are very close to the natural environment. Most poor families are dependent on nature for their survival, grazing cattle, collecting water and fuelwood and similar tasks, which are considered inferior and suitable for women and children, are not remunerative. Adult males and some women work outside for a livelihood. The life of rural women, particularly tribal women, is so much intertwined with the environment, that the whole ecosystem revolves around them and they cannot even think of their survival without it. However, significant intra-household differences in the distribution of such activities between male and female members of the families exist, varying with socioeconomic background, cultural and religious beliefs and underlying attitudes towards women and children. This article examines to what extent women in rural Jharkhand are involved in such natural resource collection and management activities. We tried to unearth the impact of cultural and economic factors on women's role in different economic sections and social groups. The analysis reveals that income, occupation and status of the families have a significant inverse link with the involvement of women and also of girl children at the cost of their educational prospects. Religious and cultural beliefs also determine the extent of women and children's involvement in resource collection. The study indicates the low empowerment level of rural women in the area.